Marx tra classicizzazione e filologia - Azzarà, Stefano G. (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2025)
This text examines the risk of “musealization” accompanying the philological work and classicization of Marx's thought, which could neutralize its subversive potential by integrating it into a harmonious and conciliatory cultural landscape. This danger is particularly acute in the West, where the absence of a revolutionary subject contrasts with the growing relevance of Marx's crisis analysis. However, the author recognizes that Roberto Fineschi's work avoids this trap by skillfully linking philology with theory and history, and by distinguishing—without separating—Marx from Marxism. The result is an approach that allows us to "start again from Marx" to understand the present, without falling into either sterile celebration or the myth of a "return" to a purified Marx. Marx; Classicization; Philology; Musealization; Globalization.